Discalculia: história, memória, (trans)form(ação) - Farias, Raene Galvão (2023)
Dyscalculia is a specific deficiency in arithmetic learning that occurs in individuals without necessarily neurological, psychiatric, sensory and emotional disorders. In line with this, we can see in the space-time of/in everyday school life numerous difficulties faced by students related to the ability to solve mathematical problems and certain calculation skills – do these difficulties arise from Dyscalculia? It is understood that at the center of a historiographical investigation with narratives, reflections on dyscalculic students are necessary, giving visibility to the eyes of the educational system, especially to the Mathematics teacher, who can take assertive actions for these students in the classroom context. Armed with this premise, the general objective of this investigation was defined, which consists of preparing a historical narrative of the processes of identification, diagnosis, intervention and inclusion of a dyscalculic student in a school in the city of Assú/RN. To this end, we rely on qualitative research, highlighting interpretations, values and human experiences. In this vein, it is linked to bibliographic and documentary research. To this end, as an instrument, interviews were used in order to reconstruct and narrate how Mathematics is taught and learned by a student who has Dyscalculia and what demands such a diagnosis from those around him. In view of this, the results presented take place on two axes: the voice of the actors, those who experience Dyscalculia – parents, students, teachers, psychopedagogues – described the (trans)formation(action) of their practices, in the face of reality personal experience and, an Educational Product – a video – that brings, through Cordel Literature, the existence of dyscalculics in schools, highlighting the importance of this diagnosis, of their families and school members. The first is developed from a discussion intertwined with intertextuality. The second, in turn, went through an analysis process with Mathematics teachers, pedagogues and Mathematics course graduates, with the aim of investigating, in the final step, the relevance of the aforementioned production, as well as possible adjustments. Given the discussions and reflections raised throughout this study, we concluded that, with the narrative, we were able to perceive contributions to the understanding of the processes of identification, diagnosis, intervention and inclusion of students in the school context, as based on the statements of the interviewees, we reflected the importance of accompanying the student from their first school activities, so that these can lead to an accurate diagnosis with professionals who work in this scenario. Furthermore, the school will allow itself to be a driving force, together with the family, so that there are pedagogical interventions in the construction of knowledge about dyscalculics. Furthermore, inclusion gains centrality. This, in turn, is a preponderant axis capable of making the dyscalculic student immersed in school and social spaces